Modulations of bioactive lipids and their receptors in postmortem Alzheimer’s disease brains - Makoto Kurano; Yuko Saito; Baasanjav Uranbileg; Daisuke Saigusa; Kuniyuki Kano; Junken Aoki; Yutaka Yatomi (Frontiers in Aging Neuroscience, 2022)
BackgroundAnalyses of brain samples from Alzheimer’s disease (AD) patients may be expected to help us improve our understanding of the pathogenesis of AD. Bioactive lipids, including sphingolipids, glycerophospholipids, and eicosanoids/related mediators have been demonstrated to exert potent physiological actions and to be involved in the pathogenesis of various human diseases. In this cross-sectional study, we attempted to elucidate the associations of these bioactive lipids with the pathogenesis/pathology of AD through postmortem studies of human brains.MethodsWe measured the levels of glycerophospholipids, sphingolipids, and eicosanoids/related mediators in the brains of patients with AD (AD brains), patients with Cerad score B (Cerad-b brains), and control subjects (control brains), using a liquid chromatography-mass spectrometry method; we also measured the mRNA levels of specific receptors for these bioactive lipids in the same brain specimens.ResultsThe levels of several species of sphingomyelins and ceramides were higher in the Cerad-b and AD brains. Levels of several species of lysophosphatidic acids (LPAs), lysophosphatidylcholine, lysophosphatidylserine, lysophosphatidylethanolamine (LPE), lysophosphatidylinositol, phosphatidylcholine, phosphatidylserine (PS), phosphatidylethanolamine (PE), phosphatidylinositol, and phosphatidylglycerol were especially high in the Cerad-b brains, while those of lysophosphatidylglycerol (LPG) were especially high in the AD brains. Several eicosanoids, including metabolites of prostaglandin E2, oxylipins, metabolites of epoxide, and metabolites of DHA and EPA, such as resolvins, were also modulated in the AD brains. Among the lipid mediators, the levels of S1P2, S1P5, LPA1, LPA2, LPA6, P2Y10, GPR174, EP1, DP1, DP2, IP, FP, and TXA2r were lower in the AD and/or Cerad-b brains. The brain levels of ceramides, LPC, LPI, PE, and PS showed strong positive correlations with the Aβ contents, while those of LPG showed rather strong positive correlations with the presence of senile plaques and neurofibrillary tangles. A discriminant analysis revealed that LPG is especially important for AD and the LPE/PE axis is important for Cerad-b.ConclusionsComprehensive lipidomics, together with the measurement of lipid receptor expression levels provided novel evidence for the associations of bioactive lipids with AD, which is expected to facilitate future translational research and reverse translational research.